THE INFLUENCE OF GROUP GUIDANCE ON THE PANTUN MAP GAME TECHNIQUE ON IMPROVING THE MANNERS OF STUDENTS IN CLASS X DPB SMK NEGERI 7 YOGYAKARTA - Santoso, Imam; Pranowo, Taufik Agung (Jurnal Konseling Pendidikan Islam, 2024)
This research aims to determine the effect of group guidance services using the rhyme map game technique on improving the manners of class X DPB students at SMK Negeri 7 Yogyakarta. This research uses a pre-experimental design with a one-group pretest-posttest design, namely experimental research with one experimental group and 3 treatments. The population in this study were students of class X DPB and X AKL 2 SMK Negeri 7 Yogyakarta. The sampling technique used is Nonprobability Sampling with Purposive Sampling type. This research uses two variables, namely group guidance on rhyme map game techniques (X) and improving manners (Y). The data collection technique for this research uses a questionnaire with one instrument, namely the polite speech scale. The data analysis technique used is t-test analysis. The research results showed that the average pretest score before being given treatment was 84.13, while the average posttest score after being given treatment was 111.63. The difference between the student manners questionnaire before and after treatment was 27.5. Based on the results of the t-test analysis, the value of t = 10.090 was obtained with a value of p = 0.000 < 0.05, which means that guiding the pantun map game technique group affected improving the manners of class X DPB students at SMK Negeri 7 Yogyakarta.